The efficacy of addition of dexmedetomidine to intrathecal bupivacaine in lower abdominal surgery under spinal anesthesia - Milad Minagar; Ebrahim Aliganpour; Ali Jabbari; Seyed Mozaffar Rabiee; Nadia Banihashem; Parviz Amri; Mehrafza Mir; Mohammad Taghi Hedayati Goudarzi; Mohammad Esmaeili (Babol University of Medical Sciences, 2019)
Background: Spinal anesthesia is the common choice for anesthesia in lower abdomen surgery and intrathecal adjutants have gained popularity with the aim of prolonging the duration of block, quality of block and post operation pain control. The purpose of this study was to evaluate the effects of adding dexmedetomidine to hyperbaric bupivacaine in lower abdominal surgery under spinal anesthesia. The main outcomes were considered pain score, duration of analgesia, hemodynamic changes and adverse side effects like nausea and vomiting. Methods: This double-blind randomized clinical trial was conducted on one hundred patients between 18 to 65 years old scheduled for lower abdominal surgery. Fifty patients were randomly allocated to receive either 12.5mg hyperbaric bupivacaine (2.5cc) plus 5µgr dexmedetomidine (0.5cc) intrathecally while fifty patients received either 12.5mg hyperbaric bupivacaine (2.5cc) and 0.5cc Saline 0.9% intrathecally. Results: Vital sign parameters like heart rate, blood pressure and oxygen saturation levels were registered in the normal range in both groups. The average duration of the onset of pain (230±86 min) in bupivacaine group was significantly (p≤0.000) less than dexmedetomidine group (495±138 minutes). The severity of pain at all times in dexmedetomidine group was significantly (p<0.05) less than bupivacaine group. The severity of shivering and the number of patients who needed treatment for nausea and vomiting in dexmedetomedine group has been less in comparison to bupivacaine. Conclusion: We concluded that intrathecal dexmedetomidine increases the duration of analgesia and reduces postoperative pain without changes in the hemodynamic parameters and adverse side effects. It can be considered as an appropriate adjuvant to intrathecal local anesthetics for lower limb surgeries.